A survey of commitment and passion among nurses in residential aged care - Phillips, Jane; Davidson, Patricia; Ollerton, Richard; Jackson, Debra; Kristjanson, Linda (Mark Allen Publishing Ltd, 2007)
Aim: To assess the views and attitudes of aged care staff providing direct care towards palliative care and to identify their learning needs. Design: Survey design using purposive sampling methods. Findings: Nurses and care assistants (n=222) employed within nine residential aged care facilities in regional Australia completed the survey. The majority had received "on the job training" and were committed to providing end-of-life care. Differences in the level of confidence to deal with patient/family interactions and manage complex palliative care scenarios were evident between nurses and care assistants (p<0.05). Both nurses and care assistants perceived a need for further education in symptom management and communication, yet their content need differed significantly between groups. Conclusions: Nurses and care assistants in residential aged care facilities demonstrate commitment to the delivery of palliative care and express a need for increased palliative care competencies. The heterogeneity of roles and educational preparation within the aged care workforce indicate that tailored palliative care education initiatives are required to meet the learning needs of aged care nurses and care assistants, particularly in relation to end-of-life care. These data have implications for skill-mix and model of care development.